Sustainability of Waqf Muhammadiyah: A Historical Study from Past to Present - Junarti, Junarti; Alhabshi, Syed Musa; Mardika, Isnan Hari; Anwar, Saiful (The International Journal of Business Review (The Jobs Review), 2021)
Waqf has an essential role in the successful development of the Persyarikatan Muhammadiyah. In addition to religious services, the Muhammadiyah Persyarikatan attempt to use waqf land for social and educational establishments. Report of the Councils of the Central Board of Muhammadiyah 2010- 2015 (PP-Muhammadiyah, 2015) on the development of Muhammadiyah's charitable efforts, particularly in education, health, and public welfare economic, and da'wah. Furthermore, there are around 3,717 ha of waqf assets and fix managed by the Muhammadiyah organization. Muhammadiyah movement succeeds to manage Waqf for social welfare. However, many people are not familiar with the basic ideas of Waqf for the charitable effort by KH. Ahmad Dahlan. The study of this scientific paper uses a qualitative paradigm with reviews literature to examine the history and phenomena of Waqf Muhammadiyah from aspects of personality and thoughts and ideas of KH. Ahmad Dahlan revealed the external acts (words and deeds) in developing Muhammadiyah in Indonesia. Furthermore, it provides descriptive data to present the condition of waqf Muhammadiyah from history until the present. Lastly, this study concludes that the community's trust for Waqf in Muhammadiyah is still very high. The future of Waqf Muhammadiyah is the chain of the past and the present.